Inverse simulated annealing for the determination of amorphous structures - Los, Jan H.; Kuehne, Thomas D. (Physical Review B - Condensed Matter and Materials Physics, 2013)
We present an efficient optimization method to determine the structure of disordered systems in agreement with available experimental data. Our approach permits the application of accurate electronic structure calculations within the structure optimization. This technique is demonstrated within density functional theory by the calculation of a model of amorphous carbon. © 2013 American Physical Society.
CRIS-Team Scopus Importer:2023-03-20